Olfactory Receptors in Non-Chemosensory Organs: The Nervous System in Health and Disease - Ferrer, Isidro; Garcia-Esparcia, Paula; Carmona, Margarita; Carro, Eva; Aronica, Eleonora; Kovacs, Gabor G.; Grison, Alice; Gustincich, Stefano (Frontiers in Aging Neuroscience, 2016)
Olfactory receptors (ORs) and down-stream functional signalling molecules adenylyl cyclase 3 (AC3), olfactory G protein α subunit (Gαolf), OR transporters Receptor Transporter Proteins 1 and 2 (RTP1 and RTP2), Receptor Expression Enhancing Protein 1 (REEP1), and UDP-glucuronosyltransferases (UGTs) are expressed in neurons of the human and murine central nervous system. In vitro studies have shown that these receptors react to external stimuli and therefore are equipped to be functional. However, ORs are not directly related to the detection of odours. Several molecules delivered from the blood, cerebrospinal fluid, neighbouring local neurons and glial cells, distant cells through the extracellular space, and the cells’ own self-regulating internal homeostasis can be postulated as possible ligands. Moreover, a single neuron outside the olfactory epithelium expresses more than one receptor, and the mechanism of transcriptional regulation may be different in olfactory epithelia and brain neurons. OR gene expression is altered in several neurodegenerative diseases including Parkinson disease (PD), Alzheimer disease (AD), Progressive Supranuclear Palsy (PSP) and sporadic Creutzfeldt-Jakob disease (sCJD) subtypes MM1 and VV2 with disease-, region- and subtype-specific patterns. Altered gene expression is also observed in the prefrontal cortex in schizophrenia with a major but not total influence of chlorpromazine treatment. Preliminary parallel observations have also shown the presence of taste receptors (TASRs), mainly of the bitter taste family, in the mammalian brain, whose function is not related to taste. TASRs in brain are also abnormally regulated in neurodegenerative diseases. These seminal observations point to the need for further studies on ORs and TASRs chemoreceptors in the mammalian brain.